2018
DOI: 10.3390/su10041040
|View full text |Cite
|
Sign up to set email alerts
|

A Global Synthesis Reveals Gaps in Coastal Habitat Restoration Research

Abstract: Abstract:Coastal ecosystems have drastically declined in coverage and condition across the globe. To combat these losses, marine conservation has recently employed habitat restoration as a strategy to enhance depleted coastal ecosystems. For restoration to be a successful enterprise, however, it is necessary to identify and address potential knowledge gaps and review whether the field has tracked scientific advances regarding best practices. This enables managers, researchers, and practitioners alike to more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 77 publications
3
61
0
Order By: Relevance
“…Restoration of seagrasses that includes the simultaneous planting of both primary and secondary foundation species such as seagrasses and bivalves is likely to yield greater biodiversity. Greater emphasis should be placed on the enhancement of habitat cascade units (secondary foundation species/ecosystem engineers) and whole ecosystems, not just primary foundation species, that promote positive interactions and ecosystem functioning [74]. We suggest that future ecological studies and conservation actions further incorporate facilitation cascades, as they are likely key but underappreciated drivers of spatial and temporal variation of biodiversity and function in seagrass beds.…”
Section: Discussionmentioning
confidence: 97%
“…Restoration of seagrasses that includes the simultaneous planting of both primary and secondary foundation species such as seagrasses and bivalves is likely to yield greater biodiversity. Greater emphasis should be placed on the enhancement of habitat cascade units (secondary foundation species/ecosystem engineers) and whole ecosystems, not just primary foundation species, that promote positive interactions and ecosystem functioning [74]. We suggest that future ecological studies and conservation actions further incorporate facilitation cascades, as they are likely key but underappreciated drivers of spatial and temporal variation of biodiversity and function in seagrass beds.…”
Section: Discussionmentioning
confidence: 97%
“…If restoration is going to be a primary mechanism for wetland recovery, as conservation organizations have proposed, we need to improve restoration efficiency (e.g., the cost to amount of restored habitat ratio) and implement restoration designs that support the rapid creation of natural, highfunctioning wetlands. Although restoration ecology often draws from ecological theory and understanding (Palmer et al, 1997;Young et al, 2005), marine managers often do not integrate important ecological concepts (e.g., positive species interactions) into restoration projects, which may mean coastal wetland restoration is underperforming (e.g., Shaver and Silliman, 2017;Zhang et al, 2018).…”
Section: The Role Of Restoration In the Future Of Coastal Wetlandsmentioning
confidence: 99%
“…Recent studies have shown that promoting positive interactions between individuals of the same species can increase restoration success (de Paoli et al, 2017; Silliman et al, 2015; van der Heide et al, 2007), highlighting the importance of facilitative interactions in restoring ecosystem‐engineering species (Maxwell et al, 2017). Facilitative interactions between ecosystem engineers may be equally important for promoting resilience and recovery (Angelini et al, 2016; Derksen‐Hoojiberg et al, 2018; Renzi, He, & Silliman, 2019; van de Koppel et al, 2015), but <3% of restoration projects have integrated interspecific interactions (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%